The Limits of World Literature. Issue 9 (September 2016) - Holmes, Christopher
Abstract: This essay examines recent work on world literature theory, with a particular focus on those theorists who treat individual texts as in dialogue with the circulations of linguistic and cultural translation. I treat world literature as the theory without an object and make the counterintuitive claim that its objectlessness makes it well suited for leaving behind antiquated modes of categorizing and canonizing so‐called world texts, in order to make room for new kinds of structured thinking about the world. The essay begins with an introduction to the manifold interconnections of the new world literature, including its broad overlap with fields of globalization, translation studies, comparative literature, and postcolonialism. I position four key theorists of 21st century world literature –Emily Apter, Rebecca Walkowitz, Berthold Schoene, andDavid Palumbo‐Liu – in oppositional pairs in order to show the underlying commonality in their thinking about the value of a literature of and for the world. My entry point into the "thinking machine" of the world literature text is the concept of the limit. Far from the commonplace understanding of limit as a limitation or boundary, I argue that understanding world literature at the limit allows literary texts and theory to be read as an event of thinking that is in‐process, in‐common, and incomplete, an analogue to the necessary impossibility of knowing the world.